Digital gaming in class: English medical terminology for pharmacy students - Mercanoglu, Guldem; Yuksel, Gulru (INTERNATIONAL PHARMACEUTICAL FEDERATION, 2022)
Objective: Knowledge of medical terminology is crucial for pharmacy students since they will be working as frontline healthcare professionals. Today's younger generation enjoys using digital tools for self-study purposes. This study aimed to investigate the impact of in-class digital game-based activities on pharmacy students' medical terminology learning performance and explore their perceptions. Method: The experiment was conducted with two classes of second-year pharmacy students over a period of 15 weeks in an English for Professional Purposes course. Data were collected using two medical word tests and a post-treatment perception questionnaire. Results: Students who learned the medical words through in-class digital gaming gained more words. This group of students also found the digital tool to be more effective and easier to use. Conclusion: In-class digital gaming is a more beneficial approach to teaching medical terminology. Integrating digital games into teaching practices would improve the acquisition and retention of medical terms among pharmacy students.
Keywords: Digital gaming; Digital tool; In-class digital gaming; Medical terminology; SCHOOL ENGAGEMENT; KNOWLEDGE; MANAGEMENT; IMPACT; GAMES; Education & Educational Research